Shared Visions: Reflections of a Blind Docent - Schmeidler, Judith Kahn (Disability Studies Quarterly, 2013)
Can a blind person serve as a museum docent? This personal account proves that it is possible and rewarding. The author shares her experience of lost vision due to Retinitis Pigmentosa, and the challenges she meets in order to continue as a docent at a museum that she loves. Key words:Blind docent,Retinitis Pigmentosa, Jewish Museum